2002
DOI: 10.1197/aemj.9.8.767
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypertension on Uncontrolled Hemorrhage in a Rodent Model

Abstract: Patients with essential hypertension (EH) have higher mortality rates from hemorrhage. How the complex physiologic changes seen in EH affect the response to uncontrolled hemorrhage has yet to be adequately described. Objective: To test the null hypothesis that there would be no difference in the hemorrhage volumes and hemodynamic responses to uncontrolled hemorrhage between hypertensive rats (SHRs) and normotensive rats (WKYs). Methods: Twenty-four adult rats (12 WKYs and 12 SHRs) were anesthetized with althes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our observations are in parallel with other findings that reported HT rats as compared with NT group, had higher mortality rate after the same vascular injury, however, post-hemorrhage blood pressure and base excess were not different between groups 3 . Another study also demonstrated that hypertensive animals experienced more profound hemorrhagic shock compared with nor-motensive animals 15 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our observations are in parallel with other findings that reported HT rats as compared with NT group, had higher mortality rate after the same vascular injury, however, post-hemorrhage blood pressure and base excess were not different between groups 3 . Another study also demonstrated that hypertensive animals experienced more profound hemorrhagic shock compared with nor-motensive animals 15 .…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we used uncontrolled hemorrhagic shock model. In this model, in spite of catheter controlled hemorrhagic model, vascular injury (amputation of tail) results in continued blood loss 3 . Experimental and clinical studies indicated that there is a defect in hemodynamic and baroreflex responses after hemorrhage in hypertensive subjects 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations